2019
DOI: 10.3390/ijerph16173217
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of School Children’s Handwashing: A Study in Tibetan Primary Schools

Abstract: Hand hygiene, including handwashing by children, has been reported to contribute to the prevention of various infectious conditions. This study aims to explore the correlates of handwashing behavior among 1690 fourth to sixth grade primary school students in 19 Tibetan primary schools (Golog, Qinghai, China). The theory of reasoned action (TRA) was applied. Data was collected by questionnaire. Structural equation modeling (SEM) analysis showed that students’ attitude (β = 0.22, 95% CI 0.13–0.31) and subjective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…This is because most children in this age group have not yet developed the cognitive ability to consciously practise the recommended prevention measures. Sun et al ( 24 ) showed that teachers had significantly more influence over a primary school student's handwashing habits before meals, and after using toilets or touching dogs, compared with family and peers. This suggests that promoting handwashing behaviours amongst students through teacher-involved participatory hygiene education may assist in preventing infectious disease transmission.…”
Section: Discussionmentioning
confidence: 99%
“…This is because most children in this age group have not yet developed the cognitive ability to consciously practise the recommended prevention measures. Sun et al ( 24 ) showed that teachers had significantly more influence over a primary school student's handwashing habits before meals, and after using toilets or touching dogs, compared with family and peers. This suggests that promoting handwashing behaviours amongst students through teacher-involved participatory hygiene education may assist in preventing infectious disease transmission.…”
Section: Discussionmentioning
confidence: 99%
“…Social norms have been found to be a strong determinant of handwashing behavior, including among children. 62 , 79 82 A study in Bangladesh reported that children were more likely to practice HWWS after visiting the toilet when a peer monitor was present, 83 and a study in Kenya that found hand cleaning rates were higher when at least 1 other person was present at the handwashing station. 84 The evidence on using motivational drivers in HWWS interventions mostly results from interventions targeting adults.…”
Section: Discussionmentioning
confidence: 99%
“…The theoretical foundation of this research is the Technology Acceptance Model (TAM), which was first developed to investigate how new technology adoption occurs [16], [17]. The Theory of Reasoned Action (TRA), which focuses on how individuals assess the value and benefits of blockchain technology, forms the basis of this model [18], [19]. Usability-related aspects are used to measure the extent to which the new technology can improve student performance, while ease-of-use aspects are used to evaluate how accessible the technology is.…”
Section: Methodsmentioning
confidence: 99%